JWST NIRCam Photometry: A Study of Globular Clusters Surrounding Bright Elliptical Galaxy VV 191a at z = 0.0513 - Jessica M. Berkheimer; Timothy Carleton; Rogier A. Windhorst; William C. Keel; Benne W. Holwerda; Mario Nonino; Seth H. Cohen; Rolf A. Jansen; Dan Coe; Christopher J. Conselice; Simon P. Driver; Brenda L. Frye; et al. (The Astrophysical Journal Letters, 2024)
James Webb Space Telescope NIRCam images have revealed 154 reliable globular cluster (GC) candidates around the z = 0.0513 elliptical galaxy VV 191a after subtracting 34 likely interlopers from background galaxies inside our search area. NIRCam broadband observations are made at 0.9–4.5 μ m using the F090W, F150W, F356W, and F444W filters. Using point-spread-function-matched photometry, the data are analyzed to present color–magnitude diagrams and color distributions that suggest a relatively uniform population of GCs, except for small fractions of reddest (5%–8%) and bluest (2%–4%) outliers. GC models in the F090W versus (F090W–F150W) diagram fit the NIRCam data well and show that the majority of GCs detected have a mass of ∼10 ^6.5 M _⊙ , with metallicities [Fe/H] spanning the typical range expected for GCs (−2.5 ≲ [Fe/H]≲ 0.5). However, the models predict ∼0.3–0.4 mag bluer (F356W–F444W) colors than the NIRCam data for a reasonable range of GC ages, metallicities, and reddening. Although our data do not quite reach the luminosity function turnover, the measured luminosity function is consistent with previous measurements, suggesting an estimated peak at m _AB ∼ −9.4 ± 0.2 mag in the F090W filter.